2017
DOI: 10.1177/0972150917692186
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Scale: Adaptation and Validation Among Indian IT (Information Technology) Employees

Abstract: Job satisfaction (JS) of employees has been studied in the past by various researchers beginning in the 1930s till date. Each of these research works went on to add a perspective to JS and its measurement. The measures of JS captured various dimensions from Minnesota satisfaction questionnaire to JS survey. Further, these measures have been standardized on working professionals in various domains except the emerging field of information technology (IT). The purpose of this study was to develop and adapt a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Along with employee turnover, employee satisfaction can show how effective the motivation system is. The research dedicated to the study of IT employee satisfaction has demonstrated that, along with salary and guarantees, training and recognition play an important role (Sharma et al, 2017).…”
Section: Theoretical Framework and Methodologymentioning
confidence: 99%
“…Along with employee turnover, employee satisfaction can show how effective the motivation system is. The research dedicated to the study of IT employee satisfaction has demonstrated that, along with salary and guarantees, training and recognition play an important role (Sharma et al, 2017).…”
Section: Theoretical Framework and Methodologymentioning
confidence: 99%
“…Job satisfaction is one of the most researched variables in organizational behaviour (Sharma, Misra, & Mishra, 2017), as it is a determinant of retention (Steil, Penha, & Bonilla, 2016;Gallardo-Gallardo & Thunnissen, 2016).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Based on the study's aim and objectives, an electronic survey was developed to collect data on (1) emotional labor, the instrument of which was developed by Gandey and Dfendorff [55]; (2) self-efficacy, the instrument of which was Schwarzer and Jerusalem's Perceived Self-Efficacy Scale [56]; (3) job satisfaction, the instrument of which was developed based on Sharma et al's work [57]; (4) life satisfaction, the instrument of which was built by Diener et al [58]; and (5) participants' socio-demographic profile, including gender, age, years of work experience, marital status, working category, and education level (Table 1). A 5-point Likert-type response scale was used for these items (from 1 = strongly disagree to 5 = strongly agree).…”
Section: Data Collectionmentioning
confidence: 99%